ADAPTATION TECHNIQUES. WAWRZYNIEC CHLEBOWSKI’SKRWAWA OFIARA JEZUSA CHRYSTUSA SYNA BOŻEGO AS A TESTIMONY OF THE RECEPTION OF ABRAHAM ROŻNIATOWSKI’S PAMIĄTKA KRWAWEJ OFIARY JEZUSA CHRYSTUSA SYNA BOŻEGO - Kuran, Michał (Prace Polonistyczne, 2021)
The article argues that Krwawa ofiara Jezusa Chrystusa Syna Bożego (The Bloody Sacrifice of Jesus Christ, the Son of God, 1616, 1621) by Wawrzyniec Chlebowski was not plagiarised from Pamiątka krwawa ofiary Jezusa Chrystusa Syna Bożego (The Memorial of the Blood Sacrifice of Jesus Christ the Son of God, 1610) by Abraham Rożniatowski. It argues that in terms of literary dependency Krwawa ofiara offers examples of imitation and compilation techniques. Moreover, the article indicates that the text does not plagiarize a short adaptation of Rożniatowski’s Pamiątka krwawa published under the title Zwierciadło (The Mirror, 1618). In my comparative analysis I have used the Open Anti-Plagiarism System (OSA). Chlebowski imitated the general pattern set by Rożniatowski, but introduced a number of additions, shortened or reorganised some parts, and replaced some elements with others. He also modified the original structure to create a handy and up-to-date meditation prayer-guidebook of the paths of the Calvary. The imitation strategies are visible on both the micro and the macro levels of the text whose reader becomes an active witness, a co-participant in Christ’s Passion and death.